The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1128/aac.47.10.3195-3201.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP Signaling Pathway Modulates Susceptibility of Candida Species and Saccharomyces cerevisiae to Antifungal Azoles and Other Sterol Biosynthesis Inhibitors

Abstract: Azoles are widely used antifungals; however, their efficacy is compromised by fungistatic activity and selection of resistant strains during treatment. Recent studies demonstrated roles for the protein kinase C and calcium signaling pathways in modulating azole activity. Here we explored a role for the signaling pathway mediated by cyclic AMP (cAMP), which is synthesized by the regulated action of adenylate cyclase (encoded by CDC35 in Candida albicans and CYR1 in Saccharomyces cerevisiae) and cyclase-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 39 publications
4
56
0
Order By: Relevance
“…In the present study, we aimed to further unravel the molecular basis of reduced susceptibility or increased tolerance of C. albicans biofilm cells to miconazole. To this end, we determined the miconazole sensitivity of biofilms of C. albicans mutants affected in cyclic AMP signalling, as it was previously reported that the cAMP signalling pathway is involved in the tolerance of planktonic C. albicans cells to miconazole (Jain et al, 2003). In addition, we validated the obtained in vitro data in an in vivo biofilm model, in which we administered miconazole intraperitoneally to rats (Ricicová et al, 2010).…”
Section: Introductionmentioning
confidence: 57%
“…In the present study, we aimed to further unravel the molecular basis of reduced susceptibility or increased tolerance of C. albicans biofilm cells to miconazole. To this end, we determined the miconazole sensitivity of biofilms of C. albicans mutants affected in cyclic AMP signalling, as it was previously reported that the cAMP signalling pathway is involved in the tolerance of planktonic C. albicans cells to miconazole (Jain et al, 2003). In addition, we validated the obtained in vitro data in an in vivo biofilm model, in which we administered miconazole intraperitoneally to rats (Ricicová et al, 2010).…”
Section: Introductionmentioning
confidence: 57%
“…In yeast, Ras activation leads to cAMP production and activation of protein kinase A. A link between cAMP-PKA signaling pathway and miconazole sensitivity in yeast has previously been reported (14); it was demonstrated that yeast mutants affected in cAMP-PKA signaling were hypersensitive toward miconazole and the observed miconazole hypersensitivity of these mutants could be partially restored by exogenous addition of cAMP (14). Whether miconazole activates Ras signaling in yeast, resulting in elevated cAMP levels and ROS levels via actin-mediated mitochondrial dysfunction, needs to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, yeast mutants affected in genes involved in DNA synthesis and repair, transcription, and chromatin structure (including ADA/Spt-Ada-Gcn5-acetyltransferase (SAGA) histone acetyltransferase complexes or SWI/SNF nucleosome remodeling complex) were previously identified as hypersensitive to a variety of stresses, including oxidative and chemical stress (14,15,16). This finding highlights the requirement for de novo transcription in response to environmental stress.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of calcineurin-mediated calcium signaling augments the effect of azoles and makes them fungicidal in Saccharomyces cerevisiae, C. albicans, C. glabrata, and C. krusei (10,18,19). Additionally, C. albicans and S. cerevisiae mutants disrupted for genes involved in cyclic AMP/protein kinase A signaling pathway are hypersusceptible to fluconazole (20). Furthermore, genetic or chemical abrogation of function of a highly conserved chaperone Hsp90 leads to antifungal drug susceptibility in diverse fungi (21).…”
mentioning
confidence: 99%